Predictors of Staphylococcus aureus and Staphylococcus pseudintermedius infections at a veterinary hospital in Malaysia - Afshar, Mohammad Farzad; Zakaria, Zunita; Cheng, Chen Hui; Ahmad, Nur Indah (Malaysian Society for Microbiology, 2024)
Aims: This study was aimed to identify the risk factors associated with the spread of Staphylococcus aureus and S. pseudintermedius isolated from dogs, cats and humans who visited a veterinary hospital. Methodology and results: A questionnaire was employed to address potential risk factors among dogs, cats and their owners, with a total of 375 samples collected. The data from the questionnaire was analysed using Fisher’s exact test and multivariable logistic regression. Six (4.8%) owners, 7 (9.3%) pet dogs and 4 (8%) pet cats were positive for S. pseudintermedius and 2 (4%) pet cats and 2 (1.6%) owners were positive for S. aureus. Keeping other pets in a house where humans also live and cats that lick the face of owners were among the significant risk factors in the carriage of S. pseudintermedius. Conclusion, significance and impact of study: It was found that the presence of other pets in the home and the habit of cats licking the faces of their owners were among the risk factors that resulted in a significant association with S. pseudintermedius in pet cats. Research findings suggest that the close contact between pets and their owners resulted in a higher rate of colonisation of S. aureus and S. pseudintermedius.